1981
DOI: 10.1017/s0016672300020127
|View full text |Cite
|
Sign up to set email alerts
|

Controlling elements in the mouse: IV. Evidence of non-randomX-inactivation

Abstract: The non-random X chromosome expression that has been observed with coat markers in female mice heterozygous for the Xce alleles, Xce a and Xce b , has now been investigated with the electrophoretic enzyme marker, Pgk-1. Because the Xce status of the Pgk-l a marked chromosome was not known, PGK expression was assessed in Pgk-l a /Pgk-l b heterozygotes which carried either Xce a or Xce b on their Pgk-l b chromosome. The PGK-1A allozyme was found to predominate in both genotypes but when Xce b was present on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
73
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 34 publications
9
73
0
1
Order By: Relevance
“…Xce has three well characterized alleles which can be classified as a gradient of strength: Xce c Ͼ Xce b Ͼ Xce a . 45 The heterozygotes exhibit NRXI. Xce maps within or in the vicinity of the Xic (X-chromosome inactivation center), 46 and it has been shown biochemically 45 and cytologically 47 to cause primary NRXI rather than secondary cell selection.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Xce has three well characterized alleles which can be classified as a gradient of strength: Xce c Ͼ Xce b Ͼ Xce a . 45 The heterozygotes exhibit NRXI. Xce maps within or in the vicinity of the Xic (X-chromosome inactivation center), 46 and it has been shown biochemically 45 and cytologically 47 to cause primary NRXI rather than secondary cell selection.…”
Section: Figurementioning
confidence: 99%
“…45 The heterozygotes exhibit NRXI. Xce maps within or in the vicinity of the Xic (X-chromosome inactivation center), 46 and it has been shown biochemically 45 and cytologically 47 to cause primary NRXI rather than secondary cell selection. Furthermore, the effects of different Xce alleles can modify the imprinted preferential inactivation of Xp in extraembryonic tissue.…”
Section: Figurementioning
confidence: 99%
“…Previous experiments have shown that Xce exerts a primary effect on choice, as skewed X inactivation patterns are observed even in embryos isolated soon after X inactivation occurs (Rastan 1982) and because the effect persists even in the face of a selective advantage for one chromosome over the other (Drews et al 1974). Three alleles of Xce have been defined in inbred mouse strains on the basis of their influence on the X inactivation pattern in genetic crosses: a weak allele Xce a (C3H/HeJ, 101/H, A/J, CBA/J and BALB/cByJ), an intermediate allele Xce b (C57BL/6J, DBA/2J and JU/Ct), and a strong allele Xce c (CAST/Ei), although additional alleles are thought to exist in other strains (Cattanach et al 1969;West and Chapman 1978;Johnston and Cattanach 1981;Simmler et al 1993). In Xce heterozygotes, the chromosome carrying the weaker of the two alleles is more likely to be inactivated.…”
mentioning
confidence: 99%
“…Although the assays to determine the Xce QTL were quite different, previous studies have found that the direction of mating either did not affect the ratio (Johnston and Cattanach 1981) or did influence the X inactivation ratios in heterozygous females (Chadwick and Willard 2005). As noted above, the direction of mating did not affect such measurements in our study of Xce heterozygous progeny.…”
Section: Analysis Of Control Micementioning
confidence: 99%
“…On the future active X chromosome, Xist is silenced during XCI. In mice, Lee and colleagues identified an antisense regulator of Xist, Tsix, whose product is also a noncoding RNA .Tsix expression represses Xist in cis and was shown to be involved in the choice process (Lee and Lu 1999 (Cattanach and Williams 1972;West and Chapman 1978;Johnston and Cattanach 1981). In heterozygous Xce a /Xce c mice, for example, the X inactivation ratio is approximately 0.25, reflecting that 25% of cells will have an active X chromosome with the Xce a allele and 75% of the cells will have an active X chromosome with the Xce c allele (Plenge et al 2000).…”
mentioning
confidence: 99%